2013
DOI: 10.1186/1471-2334-13-397
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Mycobacterium tuberculosiscomplex in patients with no known risk factors for MDR-TB in the North-eastern part of Lima, Peru

Abstract: BackgroundThe aim of this study was to investigate the genetic diversity among Mycobacterium tuberculosis complex circulating in patients with no known risk factors for multi-drug resistant (MDR) tuberculosis (TB) living in a high MDR burden area and analyze the relationship between genotypes, primary drug resistance and age.MethodsSamples were collected during January-July 2009. Isolates were tested for drug susceptibility to first-line drugs and were genotyped by spoligotyping and the 15-loci Mycobacterial I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Our results agree with this observation and previous Peruvian studies in which the Beijing family was present in relatively high proportions but was not associated with multidrug resistance (23,25,41,42). The prevailing Beijing isolates in Lima are associated with the modern subfamily coming from China, consistent with the worldwide trend except in the cases of Japan and Korea, where the ancient subfamily predominates.…”
Section: Total 754supporting
confidence: 82%
See 3 more Smart Citations
“…Our results agree with this observation and previous Peruvian studies in which the Beijing family was present in relatively high proportions but was not associated with multidrug resistance (23,25,41,42). The prevailing Beijing isolates in Lima are associated with the modern subfamily coming from China, consistent with the worldwide trend except in the cases of Japan and Korea, where the ancient subfamily predominates.…”
Section: Total 754supporting
confidence: 82%
“…Second, transmission could have occurred prior to our sampling period. When we compared our results with those of a previous study conducted in the same district in 2009 (42), however, we found few shared clusters between the two sets of samples; the 2009 study focused on low-MDR-risk patients, who did not represent the entire pool of MDR-TB cases in the area. Moreover, our study covered almost 2 years of sampling, which is considered the minimum time to study recent transmission (62).…”
Section: Total 754mentioning
confidence: 41%
See 2 more Smart Citations
“…Compared with our findings, lineages LAM (15%), Haarlem (17%) and T (20%) fit within the expected ranks. However, the number of individuals (53 or 29%) found with a X lineage is one of the highest reported to date in Mexico, and far exceeds the values reported in some Central and South American countries, such as Honduras with 6% , Peru with 4.5% , Brazil with 4.7% and Colombia with 1.7% .…”
Section: Discussionmentioning
confidence: 59%